U.K. monetary policy - Chalmers, Eric Brownlie (London : Griffith, 1968)
The book examines the implications of over reliance on monetary policy as a weapon and an instrument of economic management by the developed and the developing countries which is capable of affecting world monetary stability. It also highlights how monetary policy can be applied effectively in the management of a country economy.
Includes bibliographical footnotes and index.
usc 23/06/2017
Loans
Keywords: Monetary policy; Great Britain